The Little Book of the Shrinking Dollar : What you can do to Protect Your Money Now - Wiggin, Addison and Buker, Samantha (Hoboken John Wiley, 2012)
With the weakening dollar a hot topic for retirees, savers, and investors, this Little Book delves into the economic turmoil in the U.S. and shows how to survive it The United States dollar is losing value at an alarming rate. According to the Organisation for Economic Co-operation and Development (OECD) index, the U.S
Keywords: United States -- Dollar, American -- Purchasing power